Compact almost automorphic solutions for some nonlinear dissipative differential equations in Banach spaces. (19th May 2018) - Drisi, Nadia; Es-sebbar, Brahim; Ezzinbi, Khalil
ABSTRACT: The aim of this work is to prove the existence and uniqueness of compact almost automorphic solutions for some dissipative differential equations in Banach spaces when the input function is only almost automorphic in the sense of Stepanov. Examples and a numerical simulation are provided to illustrate the theoretical findings.